Determinants of IPO Underpricing in Indonesia (2021–2024): The Roles of Offer Size, Offer Price, Underwriter Reputation, Syndicate Size, and Market Condition - Denny Tewu; Martua Eliakim; Sri Bintang Elisabet (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the determinants of IPO underpricing in Indonesia from 2021 to 2024, emphasizing the effects of offer size, offer price, underwriter reputation, syndicate size, and market condition. Employing a quantitative descriptive–verificative design, the study analyzes secondary data from 215 IPOs listed on the Indonesia Stock Exchange using multiple linear regression (SPSS 26) after data validation and classical assumption testing. The results reveal that offer size, offer price, underwriter reputation, and syndicate size negatively influence underpricing, whereas market condition has a positive and significant impact. The model explains 61.2% of underpricing variation, reinforcing the applicability of information asymmetry and signaling theories in emerging markets.